Two new species of the genus Austerocardiochiles Dangerfield, Austin & Whitfield, 1999 (Hymenoptera: Braconidae: Cardiochilinae) from Vietnam - Long, Khuat Dang; Oanh, Nguyen Thi; Dzuong, Nguyen Van; Hoa, Dang Thi (Zootaxa, 2019)
Two new species of the genus Austerocardiochiles Dangerfield, Austin & Whitfield, 1999 from Vietnam, viz. A. mellosus Long, sp. n. and A. simulatus Long, sp. n., are described and illustrated. Additionally, the genus Austerocardiochiles is newly recorded for the braconid fauna of Vietnam. The checklist and distribution of already known species of the genus Austerocardiochiles are given. A comprehensive key to Austerocardiochiles species from Oriental region is also provided.